The Impact of Body Positivity in Fashion Advertising on Customer Perceptions and Purchase Intentions - Tsawaab, Amallia Husnuts (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The fashion business is regarded as one of the most important industries in the world and contributes significantly to the world economy’s benefits. In the era of technology, applying the right management techniques for advertising is very important to succeed among commercial competitors in competitive markets. Even though advertising has so many positive effects, it also has a negative side, such as it could create unrealistic beauty and body standards due to the marketers using attractive, slender, and tall models which promotes the ideal body image in culture. The purpose of this research is to determine how impactful body diversity in advertising affects consumers' attitude toward advertisements and their desire to buy clothes, to determine what kind of models to utilize in fashion goods commercials to strengthen consumer perceptions of advertisements and buy intent, and to explore the effects of size inclusivity as the moderating variable of diversity in advertising and attitude toward the advertisements. The methodologies used in this study were qualitative and quantitative. As a result, the purpose of this study is to determine whether or not advertising that promotes body positivity has an impact on how consumers feel about advertisements and their intentions to buy from fashion retailers, which type of model's body, a larger or slimmer one, has a greater effect on the consumer's perception of the advertising and their desire to purchase according to the customer's body type and sizes, and how size inclusivity becomes the moderating variable between advertisements and purchases.